Prolonged Absence of Mechanoluminal Stimulation in Human Intestine Alters the Transcriptome and Intestinal Stem Cell NicheSummary - Minna M. Wieck; Christopher R. Schlieve; Matthew E. Thornton; Kathryn L. Fowler; Mubina Isani; Christa N. Grant; Ashley E. Hilton; Xiaogang Hou; Brendan H. Grubbs; Mark R. Frey; Tracy C. Grikscheit (Cellular and Molecular Gastroenterology and Hepatology, 2017)
Background & Aims: For patients with short-bowel syndrome, intestinal adaptation is required to achieve enteral independence. Although adaptation has been studied extensively in animal models, little is known about this process in human intestine. We hypothesized that analysis of matched specimens with and without luminal flow could identify new potential therapeutic pathways. Methods: Fifteen paired human ileum samples were collected from children aged 2â20 months during ileostomy-reversal surgery after short-segment intestinal resection and diversion. The segment exposed to enteral feeding was denoted as fed, and the diverted segment was labeled as unfed. Morphometrics and cell differentiation were compared histologically. RNA Sequencing and Gene Ontology Enrichment Analysis identified over-represented and under-represented pathways. Immunofluorescence staining and Western blot evaluated proteins of interest. Paired data were compared with 1-tailed Wilcoxon rank-sum tests with a P value less than .05 considered significant. Results: Unfed ileum contained shorter villi, shallower crypts, and fewer Paneth cells. Genes up-regulated by the absence of mechanoluminal stimulation were involved in digestion, metabolism, and transport. Messenger RNA expression of LGR5 was significantly higher in unfed intestine, accompanied by increased levels of phosphorylated signal transducer and activator of transcription 3 protein, and CCND1 and C-MYC messenger RNA. However, decreased proliferation and fewer LGR5+, OLFM4+, and SOX9+ intestinal stem cells (ISCs) were observed in unfed ileum. Conclusions: Even with sufficient systemic caloric intake, human ileum responds to the chronic absence of mechanoluminal stimulation by up-regulating brush-border enzymes, transporters, structural genes, and ISC genes LGR5 and ASCL2.Â These data suggest that unfed intestine is primed to replenish the ISC population upon re-introduction of enteral feeding. Therefore, the elucidation of pathways involved in these processes may provide therapeutic targets for patients with intestinal failure. RNA sequencing data are available atÂ Gene Expression Omnibus series GSE82147. Keywords: Intestinal Stem Cell, LGR5, Small Intestine, Calorie Restriction, Enteric Nutrition, Mechanoluminal Flow